DOUBLE LAYER FREQUENCY SELECTIVE SURFACE WITH BROAD BANDWIDTH, HIGH SELECTIVITY AND GOOD ANGULAR STABILITY (REVUE ROUMAINE DES SCIENCES TECHNIQUES — SÉRIE ÉLECTROTECHNIQUE ET ÉNERGÉTIQUE, 2022)
A frequency selective surface (FSS) with low insertion loss, high selectivity, broad bandwidth, and good angular stability is proposed here. It is a patch-type FSS with two dielectric layers separated by an air gap of 1.6 mm. The bottom dielectric layer with an array of metallic patches is notified as the first FSS (FSS 1), and the top dielectric layer with an array of metallic patches is notified as the second FSS (FSS 2). In Model 1, the top surface of FSS 1 is an array of square ring-shaped metallic patches, and the bottom surface of FSS 2 is an array of square-shaped metallic patches. In Model 2, the top surface of FSS 1 is an array of square ring-shaped metallic patches, and the bottom surface of FSS 2 is an array of circular-shaped metallic patches, which are placed in a dual-layer configuration with a separation of 1.6 mm. Two reject bands are achieved as a result. Between two notch bands, a pass-band is achieved from 1.98 GHz to 5.29 GHz with good selectivity and angular stability. A notch is found at around the 3.6/4.6 GHz range, the operating band of Wi-MAX (3.3 - 3.6 GHz) and C band (3.7 GHz - 4.2 GHz). Another notch at 5.2/5.9 GHz band is achieved. The proposed FSS designs are helpful for WLAN applications.
Keywords: Frequency Selective Surface (FSS); Low insertion loss; Selectivity; Angular stability; Worldwide Interoperability for Microwave Access (WiMAX); C-band; Wireless local area network (WLAN)